Al-Ghazali’s Psycho-Spiritual Counseling Theory: Guidance and Counseling from the Perspective of Islamic Philosophers - Wahid, Ahmad; Karneli, Yeni; Solfema, Solfema; Qorib, Fathul (Al Musyrif: Jurnal Bimbingan dan Konseling Islam, 2025)
The rapid development of guidance and counseling science and its mutual refinement is a positive trend that needs to be continued. Likewise, Islamic counseling theories need to be introduced and implemented in the science of guidance and counseling. One of the theories that is important to know and glorify is Al-Ghazali’s psycho-spiritual counseling theory. This research aims to conduct an in-depth study of Al-Ghazali’s psycho-spiritual counseling theory. The research is oriented towards a qualitative approach, utilizing the library research method.  Furthermore, it is analyzed by using the content analysis method. The results of this study explain that Al-Ghazali’s psycho-spiritual counseling theory focuses on revamping the aspects of al-nafs, al-qalb, al-ruh, and al-’aql as an effort to alleviate individual problems. This counseling is carried out through 5 important stages, namely, building good relationships with clients, recognizing themselves and identifying the causes of problems, applying the tazkiyah al-nafs approach with the rules of mujahadah al-nafs (takhalli), applying the tazkiyah al-nafs approach with the rules of riyadah al-nafs (tahalli) and assessment. The results of this study can be one of the guidelines and credible sources regarding the implementation of Al-Ghazali’s psycho-spiritual counseling, so that it can be applied as an intervention effort in overcoming individual problems.